Unleashing ultra-fast sodium ion storage mechanisms in interface-engineered monolayer MoS2/C interoverlapped superstructure with robust charge transfer networks. Issue 30 (21st July 2020) - Wang, Lili; Zhang, Haitao; Wang, Yanlei; Qian, Cheng; Dong, Qiang; Deng, Chonghai; Jiang, Danfeng; Shu, Mengyao; Pan, Shanshan; Zhang, Suojiang
Abstract : A new MoS2 /C nanoarchitecture with robust charge transfer networks fabricated via a "self-splitting" process of bagasse exhibits ultra-fast/stable Na-ion storage. Abstract : Na-related anodes with excellent rate capability and ultra-stable cyclability are being pursued significantly to overcome the slow kinetics of currently available compounds on account that the sodium-ion battery is an ideal energy storage device technology for grid-scale electricity networks. Herein, we demonstrate a novel concept for the construction of a nanoarchitecture with robust charge transfer networks, which is composed of MoS2 /C superstructure nanoflowers embedded in carbon nanonets (MoS2 /C-CNNs). Impressively, the optimized nanoarchitecture exhibited an ultra-fast Na-ion storage feature, a superior reversible capacity of 245.2 mA h g −1 at 5 A g −1, and a promising retention of 78.9% after 8000 cycles. The interconnected 3D carbon nanonetworks, derived from the carbonization of sugarcane bagasse via a novel "self-splitting process", were found to be extremely beneficial for the acceleration of electron transport and Na + diffusion, while alleviating the volumetric strain of MoS2 during the Na + insertion/extraction processes. Furthermore, computational analysis was performed to reveal the underlaid mechanism, demonstrating that the MoS2 /C superstructures can significantly ameliorate the electronic conductivity of MoS2 and lower the Na + diffusion barrier, which tend to facilitate the electron and Na + transport at the atomic level. This work demonstrates that the construction of robust 3D ion/electron traffic networks at various scales is an efficient strategy to develop electrodes with adequate rate capability and remarkable cyclability.